Chemical Analysis and Multi-Component Determination in Chinese Medicine Preparation Bupi Yishen Formula Using Ultra-High Performance Liquid Chromatography With Linear Ion Trap-Orbitrap Mass Spectrometry and Triple-Quadrupole Tandem Mass Spectrometry - Zhang, Jing; Xu, Wen; Wang, Peng; Huang, Juan; Bai, Jun-qi; Huang, Zhi-hai; Liu, Xu-sheng; Qiu, Xiao-hui (Frontiers in Pharmacology, 2018)
Bupi Yishen Formula, a Chinese medicine preparation, has been clinically applied for the recovery of chronic kidney disease and for delaying its progress. Nevertheless, the chemical components in Bupi Yishen Formula have yet to be fully clarified. Ultra-high performance liquid chromatography with linear ion trap-Orbitrap mass spectrometry (UHPLC-LTQ-Orbitrap-MSn) and triple-quadrupole tandem mass spectrometry (UHPLC-TQ-MS/MS) methods were developed for qualitative chemical profiling and multi-components quantitative analysis in Bupi Yishen Formula. The chromatographic separation was performed on a Phenomenex Kinetex C18 column (2.1×100 mm i.d., 1.7 μm) using gradient elution of water (A) and acetonitrile (B) both containing 0.1% formic acid. Eighty-six compounds, including flavones, saponins, phenolic acids and other compounds were authenticated or temporarily deduced according to their retention behaviors, mass mensuration and characteristic fragment ions with those elucidated references or literature. Among the herbal medicinal materials of the formula, Astragali Radix, Codonopsis Radix, Salviae Miltiorrhizae Radix Rhizoma and Polygoni Multiflori Radix Praeparata contributed to the bulk of the dissolved metabolites of the formula extraction. In addition, seven analytes were simultaneously determined by UHPLC-TQ-MS/MS, which was validated and has managed to determine major components in Bupi Yishen Formula. The study indicated that the established qualitative and quantitative methods would be potent and dependable analytical tools for characterizing multi-constituent in complex prescriptions Decoction and provided a basis for the evaluation of bioactive components in Bupi Yishen Formula.